2013
DOI: 10.1254/jphs.13r01cp
|View full text |Cite
|
Sign up to set email alerts
|

The Linkage Between Coenzyme A Metabolism and Inflammation: Roles of Pantetheinase

Abstract: Abstract.Pantetheinase is an enzyme hydrolyzing pantetheine, an intermediate of the coenzyme A degradation pathway. Pantetheinase has long been considered as the enzyme that recycles pantothenic acid (vitamin B 5 ) generated during coenzyme A breakdown. Genetic analyses showed that mammals have multiple genes known as vanin family genes. Recent studies using mice lacking the vanin-1 gene (pantetheinase gene) suggest that pantetheinase is actively involved in the progression of inflammatory reactions by generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…Furthermore, although arginase activity has been correlated with the function of MDSCs [15,16], L-arginine supplementation failed to demonstrate a clinical benefit [17]. GPI-80 is suggested to work as a modulator of macrophage-1 antigen (Mac-1) (CD11b/CD18) function [18]. GPI-80 is suggested to work as a modulator of macrophage-1 antigen (Mac-1) (CD11b/CD18) function [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although arginase activity has been correlated with the function of MDSCs [15,16], L-arginine supplementation failed to demonstrate a clinical benefit [17]. GPI-80 is suggested to work as a modulator of macrophage-1 antigen (Mac-1) (CD11b/CD18) function [18]. GPI-80 is suggested to work as a modulator of macrophage-1 antigen (Mac-1) (CD11b/CD18) function [18].…”
Section: Introductionmentioning
confidence: 99%
“…XDH plays a major role in phagocytic killing47 and high expression levels are indicative of activated and infected macrophages in M paratuberculosis and is characteristic of oxidative stress. VNN1 is involved in cysteamine production, a major promotor of inflammation48 and polymorphisms of human VNN1 are linked to susceptibility to IBD49. FGF23 is expressed by activated macrophages, and elevated levels impair neutrophil recruitment50.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanism of this effect is not understood. More recently the association between CoA metabolism and inflammation has also been suggested as it has been shown that the pantetheinase enzyme that recycles pantothenic acid and pantetheinase gene (vanin-1) knockout mice has been shown to be involved in the progression of inflammatory reactions [16]. The bioavailability of pantothenic acid has been reported in the range of 40–63% and amounts found in 24-h urine samples have been shown to correlate with this intake [17].…”
Section: Discussionmentioning
confidence: 99%